Children's and adolescents' views on upper limb prostheses in relation to their daily occupations. (April 2020) - Sims, Tara; Donovan-Hall, Maggie; Metcalf, Cheryl
Introduction: Prosthetic treatment is widely used for children and adolescents with upper limb difference, for functional benefit, cosmetic restoration or the performance of specific activities. Children and adolescents feel, however, that prostheses do not help function, are uncomfortable, are unreliable, are heavy and are not aesthetically acceptable. This research aims to develop an understanding of children's and adolescents' views on upper limb prostheses in relation to their daily occupations. Method: Eight children and adolescents with upper limb difference participated in a focus group ( n =4) or an individual interview ( n =4). Data was analysed using thematic analysis. Results: Participants described both positive and negative views of their prostheses. Participants described experiences where their prosthesis was helpful to them for social interactions, when playing and in self-care and productive activities. However, participants also described choosing not to use prostheses due to lack of functional benefit, causing a hindrance in certain activities and restriction of movement. Conclusion: Prostheses can be useful tools for occupational participation for children and adolescents. General purpose functional prostheses for children and adolescents can result in the prosthesis not being useful, becoming a hindrance and restricting movement. Task specific devices can overcome these issues to help children and adolescents in social interactions, when playing and in carrying out self-care and productive activities.